DEVELOPMENT OF PROPOSALS ON RATING EVALUATION OF SELF-REGULATING ORGANIZATIONS OF ARBITRATION MANAGERS AND RELEVANT INDICATORS FOR THE IMPLEMENTATION OF THE EVALUATION - V. N. Alferov (Модернизация, инновация, развитие, 2015)
The article deals with topical issues of the effectiveness of self-regulatory organizations of arbitration managers (SRO AU) and the arbitration managers playing a key role in the bankruptcy law and financial restructuring of Russian enterprises. Despite the increasing demands imposed on the arbitration managers, professionalism and quality of their work remains low, the number of administrative offenses is not reduced. The article discusses various approaches to build-rated activities of CPO AU and the corresponding figures for the implementation of the evaluation.